Public support for renewable energy in Poland - Michał Ptak (Economic and Environmental Studies (E&ES), 2017)
The article discusses major public funding sources available to promote investments in renewable energy projects in Poland. The main sources include environmental funds that are financed from environmental charges levied on companies that cause environmental damage and operational programmes funded by European Union funds. The aim of the paper is to reveal the amount of public support for renewable energy in Poland, after comparison of funding programmes implemented by environmental funds and EU funds managing authorities. The comparison includes the level of support and impact on objectives in relation to renewable energy production and greenhouse gas emissions. Based on available information it can be concluded that the level of financial support for investments in renewable energy provided by the environmental funds and operational programmes was quite comparable in recent years. Both types of funding sources are also important instruments to foster the use of renewable energies. An important result of the support is the reduction of greenhouse gas emissions.
Keywords: H23; Q42; Q54; 330; renewable energy; climate change; environmental funds; operational programmes